2007
DOI: 10.1007/s11104-007-9355-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of hybrid poplar as affected by dandelion and quackgrass competition

Abstract: A pot experiment was conducted in a growth chamber to investigate the effects of dandelion (Taraxacum officinale) and quackgrass (Elymus repens) on the growth of hybrid poplar (Populus deltoides×Populus×petrowskyana var. Walker). Single hybrid poplar seedlings were grown in pots either alone (SHP) or with four or eight dandelion plants per pot or with one or three quackgrass plants per pot in two soils collected from sites previously managed for alfalfa and pasture near Meadow Lake, Saskatchewan, Canada. Hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…It was observed that the supply of NO 3 -N was exhausted within the simulation time, in particular for the second harvest simulations in both soils. This observation is contradictory to the measured soil solution values for the control treatment pots where significant amounts of NO 3 -N were still present in the soil solution at the end of the second harvest (Kabba et al 2007). The presence of NO 3 suggests that the availability of N to the plant is through some other pools such as N mineralization (Stevenson 1986).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It was observed that the supply of NO 3 -N was exhausted within the simulation time, in particular for the second harvest simulations in both soils. This observation is contradictory to the measured soil solution values for the control treatment pots where significant amounts of NO 3 -N were still present in the soil solution at the end of the second harvest (Kabba et al 2007). The presence of NO 3 suggests that the availability of N to the plant is through some other pools such as N mineralization (Stevenson 1986).…”
Section: Resultsmentioning
confidence: 75%
“…Details of the pot study are reported in Kabba et al (2007) and are briefly described here. Hybrid poplar seedlings were grown in pots from 7.5-cm long stem cuttings that were soaked overnight in water.…”
Section: Estimation Of Model Input Parametersmentioning
confidence: 99%
“…Predominant non-leguminous forbs in our study area included Taraxacum officinale, which is known to be a competitive species detrimental to poplar growth (Kabba et al 2007). Henkel-Johnson et al (2016) also found that forbs consistently suppressed tree diameter growth during the first three years and speculated that this was due to the tallstatured and broadleaved growth habit of forbs reducing light availability to young tree saplings.…”
Section: Discussionmentioning
confidence: 77%
“…The negative influence of PG on hybrid poplar size and annual growth was expected and agrees with findings in other studies; these effects are particularly important given that they occurred despite the intensive understory control measures implemented as part of the ongoing silviculture management of these plantations (Landhäusser andLieffers 1998, Henkel-Johnson et al 2016). Grasses have been recognized to be a limiting agent for tree growth in potted experiments due to belowground competition for root space (Messier et al 2009) and nutrient uptake (Kabba et al 2007). Field studies examining the effect of the native marsh reed grass (Calamagrostis canadensis (Michx.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation